Institutional and Structural Determinants of Investment Worldwide - Lim, Jamus Jerome (World Bank, Washington, DC, 2013)
This paper considers institutional and structural factors associated with investment activity in a panel of up to 129 developed and developing countries. It introduces these factors to a standard neoclassical investment function for open economies, and find that financial development and institutional quality are reasonably robust determinants of cross-country capital formation, with latter displaying more stability in the sign and significance of its coefficient. Indeed, when endogeneity concerns are addressed more explicitly using external instruments, and both interactions and subsamples are considered, institutional quality tends to survive as the causal determinant of investment.